The effects of summer sports school basketball training on respiratory functions of female students - Orhan, Serdar; Eskiyecek, Canan Gülbin (Horizon Research Publishing, 2018)
A total of 60 female students voluntarily participated in this study in which the exercise-dependent changes in the respiratory functions of female students in the age group of 12-16 who participate in basketball training sessions of summer sports school are analysed. 30 female students participated in summer sports school basketball training group constituted the experimental group and 30 female students in the same age group who did not participate in basketball training formed the control group. The experimental group was applied an interval training program specific to basketball 5 days a week in 12 weeks. The control group was not applied any training program at all. Some physical measurements (age, height, weight) and spirometry measurements (FVC, FVC%, FEV 1 , FEV 1 %, FEV 1 /FVC%, PEF, PEF%, FEF 25/75 , FEF 25/75 %) were recorded as preliminary and post-tests in the research. Paired Simple t-test and Wilcoxon were used in intra-group analyses of data obtained and Mann-Whitney U test was used for the intergroup comparisons. While significant difference can be established in the height, FVC, FVC%, FEV 1 , FEV 1 % and FEV 1 /FVC% values of experimental group and height values of the control group compared to the time before the training; height, weight, FVC, FVC%, FEV 1 , PEF, FEF 25/75 and FEV 1 /FVC% values of the experimental group have significantly differed from the control group. In conclusion, it can be stated that interval training programs specific to basketball and applied to the female students in summer sports school have positive effects on the respiratory functions and they can contribute to both physical and lung development of individuals. © 2018 by authors, all rights reserved.
Keywords: Basketball; Female student; Interval; Respiration; Summer sports school